Pengembangan Flipbook Panduan Praktikum Dasar Memasak sebagai Penunjang Mata Pelajaran Dasar-Dasar Kuliner - Seftiani, Vini; Artanti, Guspri Devi; Kandriasari, Annis (Peneliti.net, 2025)
This study aims to develop and test the feasibility of a basic cooking practicum guide flipbook as a support for Culinary Basics subjects. The method used in this research is Research and Development (R&D) with the 4D Thiagarajan, Semmel, and Semmel development model, which includes defining, designing, developing, and disseminating stages. The data analysis technique employed is descriptive qualitative. This learning media has been validated by material experts, media experts, and linguists, scoring 83% for material aspects indicating high feasibility, 88% for media aspects indicating high feasibility, and 95% for language aspects indicating high feasibility. The validated media was tested on students at Vocational High School 3 Bogor, yielding results of 94% in one-to-one assessments with 3 respondents (very feasible), 93% in small group tests with 10 respondents (very feasible), and 93% in field group tests with 34 respondents (very feasible). Based on these validation and testing results, it can be concluded that the development of a basic cooking practicum guide flipbook as a support for Culinary Basics subjects is highly feasible as a learning medium.